Meningkatkan Customer Engagement melalui Brand Image dan Content Visual: Perspektif pengguna DNVB di Indonesia - Wardanu, Aditya Putra; Noviarkahman Zagladi, Arief (Journal of Management and Bussines (JOMB), 2024)
This study aims to analyze the influence of Brand Image (BI), Interest Audience (IA), and Content Visual (CV) on Customer Engagement (CE) among Digitally Native Vertical Brands (DNVB) users in Indonesia. 286 samples were used in this study. The results of this study indicate that BI has a significant positive influence on CV, indicating that a good brand image contributes to a positive perception of the quality of visual content. In addition, IA also has a significant effect on CE, indicating that content that is relevant to the audience's interests can increase their engagement. The results of the analysis show that CV has a positive effect on CE, indicating that attractive visual content can encourage user interaction. This study also found an indirect effect of BI through CV and IA on CE, indicating that brand image not only has a direct impact but also through increasing audience interest and the quality of visual content. In conclusion, this study emphasizes the importance of managing brand image and presenting high-quality visual content in increasing customer engagement in today's digital era. Therefore, DNVB companies are advised to continue to improve the quality of visual content and ensure that content matches audience interests to build stronger relationships with consumers. Keywords: Brand Image, Content Visual, Interest Audience